Storing Fresh Fruits and Vegetables - Jennifer Hillan; Claudia Peñuela (EDIS)
Revised! FCS8707, a 1-page fact sheet by Jennifer Hillan and Claudia Peñuela, provides guidelines for storing fresh whole produce. Published by the UF Department of Family, Youth and Community Sciences, October 2010.